JNK activation induced by ribotoxic stress is initiated from 80S monosomes but not polysomes - Kim, Tae-Sung; Kim, Hag Dong; Park, Yong Jun; Kong, EunBin; Yang, Hee Woong; Jung, Youjin; Kim, YongJoong; Kim, Joon (BMB reports, 2019)
Translation is a costly, but inevitable, cell maintenance process. To reduce unnecessary ATP consumption in cells, a fine-tuning mechanism is needed for both ribosome biogenesis and translation. Previous studies have suggested that the ribosome functions as a hub for many cellular signals such as ribotoxic stress response, mammalian target of rapamycin (mTOR), and ribosomal S6 kinase (RSK) signaling. Therefore, we investigated the relationship between ribosomes and mitogen-activated protein kinase (MAPK) activation under ribotoxic stress conditions and found that the activation of c-Jun N-terminal kinases (JNKs) was suppressed by ribosomal protein knockdown but that of p38 was not. In addition, we found that JNK activation is driven by the association of inactive JNK in the 80S monosomes rather than the polysomes. Overall, these data suggest that the activation of JNKs by ribotoxic stress is attributable to 80S monosomes. These 80S monosomes are active ribosomes that are ready to initiate protein translation, rather than polysomes that are already acting ribosomes involved in translation elongation. [BMB Reports 2019; 52(8): 502-507].